2010
DOI: 10.1186/ar3111
|View full text |Cite
|
Sign up to set email alerts
|

Bone events and evolution of biologic markers in Gaucher disease before and during treatment

Abstract: IntroductionKnown biomarkers of Gaucher-disease activity are platelets, chitotriosidase, angiotensin-converting enzyme (ACE), tartrate-resistant acid phosphatase (TRAP) and ferritin. The aim of this study was to retrospectively evaluate the frequency of bone events (BE) and biomarker changes during two periods: diagnosis to first enzyme-replacement therapy (ERT) and the latter to the closing date.MethodsBE of 62 treated patients, among the 73-patient cohort followed at Beaujon Hospital, Clichy, France, were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
7
37
0
3
Order By: Relevance
“…Bone turnover can be measured with specific biochemical markers [60] for enzyme activities, the release of various structural components of bone, and proteins involved in the processes of bone formation (Table 5). Over the years, most of these parameters have been tested in patients with GD [33][34][35][36][37][38][39][40]. Urinary total hydroxyproline levels are used to identify osteoclastic hyperactivity.…”
Section: Biomarkers For Bone Damagementioning
confidence: 99%
“…Bone turnover can be measured with specific biochemical markers [60] for enzyme activities, the release of various structural components of bone, and proteins involved in the processes of bone formation (Table 5). Over the years, most of these parameters have been tested in patients with GD [33][34][35][36][37][38][39][40]. Urinary total hydroxyproline levels are used to identify osteoclastic hyperactivity.…”
Section: Biomarkers For Bone Damagementioning
confidence: 99%
“…(6) The most impactful and dramatic clinical complications arising from bone involvement are AVN, osteopenia, and fractures. (2,5,7,8) These complications permanently alter the health status of affected patients due to chronic pain, disability, and the need for surgical interventions. (6) The precise risk of AVN in untreated GD1 (not receiving imiglucerase therapy) was estimated to be 22.8 per 1000 person years (95% confidence interval [CI], 20.2-25.7) of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the most conspicuous form of AVN, akin to that seen in sickle cell crises, there is also a silent variety of AVN in GD1 that occurs in the form of medullary infarction due to asymptomatic vascular obstruction of medullary blood vessels; this form of AVN is detected by magnetic resonance imaging (MRI) of the bone marrow. (11) The majority of GD1 patients exhibit osteopenia, (2,5,7) measured by dual-energy X-ray absorptiometry (DXA). (12,13) Although osteopenia in GD is commonly attributed to increased osteoclastic bone resorption, (14) it is more likely related to impaired osteoblast function (15,16) associated with accumulating lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Serum CCL5/RANTES was significantly elevated in patients who had osteonecrosis and in the small group of Gaucher patients who had not met therapeutic goals, despite enzyme therapy [72]. In a retrospective survey from France, based on routine physical assessments and the results of more conventional analytes such as serum ferritin, in a cohort of 62 patients, initial ferritin concentrations and platelet counts were associated with bone events reported during enzyme therapy [75].…”
Section: Treatment Options and Their Efficacy On Osteonecrosismentioning
confidence: 99%
“…Detailed analyses of the same cohort indicated that CXCL8/IL-8 and CCL5/RANTES had the best discriminatory characteristics for osteonecrosis (Figure 4) [72]. Other putative markers have been reported to be associated with the episodes of osteonecrosis despite treatment [72,75]. CXCL8/IL-8 is implicated in leukocyte--vascular endothelial interactions and appears to mediate angiogenesis driven by cells of macrophage lineage [96,97].…”
Section: The Predictive Role Of Biomarkers 241 Biomarkers Of Osteonmentioning
confidence: 99%